Volume 26 of the Journal of the Assembly for Expanded Perspectives on Learning - Wendy Ryden (Journal of the Assembly for Expanded Perspectives on Learning, 2021)
The Assembly for Expanded Perspectives on Learning (AEPL), an official assembly of the National Council of Teachers of English, is open to all those interested in extending the frontiers of teaching and learning beyond the traditional disciplines and methodologies. JAEPL is especially interested in helping those teachers who experiment with new strategies for learning to share their practices and confirm their validity through publication in professional journals.
Keywords: Creative Writing; Curriculum; Educational Psychology; English Language; English Literature; Liberal Studies; Spirituality; Teacher Education